Overview Kepuasan Pelanggan: Studi Kasus Pelayanan Rijstaffel di Restoran Oasis - Maria Pia Adiati; Agung Gita Subakti (Bina Nusantara University, 2015)
Rijstaffel service is not common found in fine dining restaurant in Indonesia. Oasis Restaurant in Jalan Raden Saleh, Jakarta, is a restaurant that is consistent in serving rijstaffel menu. The objective of this research is to analyze the level of consumer satisfaction and service quality in rijstaffel service at Oasis Restaurant. Research used qualitative method with library research by analyzing the questionnaire distributed by Oasis on Mei 2013 with 21 respondents. The result is the indicators which got excellence point were service, ambience, value for money, food; and the indicator which got good point was home band and vocal group.